The last and largest of Cephalanthus tetrandra freshwater swamp forest in Northeast Thailand: Natural resource appreciation and management of local community - Mikhama, K.; Sirisant, P. (International Journal of Agricultural Technology, 2016)
Initial study revealed that the freshwater swamp forest of Cephalanthus tetrandra trees in Don Daeng village, Nakhon Phanom province, is the only one of its kind in Northeast Thailand. This, then, led to questions as to how the community managed the forest’s natural resources. This study found that the villagers’ appreciation of the forest for their life, socio-cultural and farming support have contributed significantly to the preservation of the forest. Two approaches were employed in the management of the forest. The direct approaches include management of the freshwater swamp forest in order to preserve C. tetrandra, preservation of the lake as a main source of water supply, water management for off-season rice farming and protection of aquatic plant and animal as well as wildlife species, while the indirect approach concerns the worship of the villagers’ ancestors’ ghosts. The active participation of the local community in simultaneous management and preservation of the lake’s natural resources should serve as a great example to other communities where C. tetrandra swamps used to be in existence.